Evaluation of two methods of the jump float serve in volleyball - MacKenzie, S. J.; Kortegaard, K.; LeVangie, M.; Barro, B. (Journal of Applied Biomechanics, 2012)
A novel jump-focused (JF) technique of the jump float serve was compared with the conventionally used contact-focused (CF) method. Seven elite male (height: 195 ± 6 cm) and two elite female (height: 181 and 182 cm) volleyball players were videoed at 60 Hz performing both techniques. Horizontal and vertical ball contact coordinates, pre- and postcontact ball velocities, and initial projection angles were determined. The JF technique resulted in a significantly higher mean contact height, t(8) = 4.12, p = .006, d = 0.72, initial serve speed, t(8) = 4.71, p = .006, d = 2.03, and significantly flatter initial projection angle, t(8) = 2.53, p = .036, d = 0.63, relative to the CF technique. The precontact vertical ball velocity was also significantly higher, t(8) = 8.04, p = .004, d = 2.86. The higher precontact vertical ball velocity suggests it is more difficult to make accurate contact with the ball during the JF technique. However, this method promotes a more favorable ball trajectory and a greater initial serve speed. When combining the random lateral movement patterns inherent in any float serve, with the reduced flight time associated with the JF technique, a more challenging passing scenario can be presented to the defensive team in comparison with the current CF technique.